Should the colonisation of space be based on reproduction? Critical considerations on the choice of having a child in space - Maurizio Balistreri; Steven Umbrello (Journal of Responsible Technology, 2022)
This paper aims to argue for the thesis that it is not a priori morally justified that the first phase of space colonisation is based on sexual reproduction. We ground this position on the argument that, at least in the first colonisation settlements, those born in space may not have a good chance of having a good life. This problem does not depend on the fact that life on another planet would have to deal with issues such as solar radiation or with the decrease or entire absence of the force of gravity. These issues could plausibly be addressed given that the planets or settlements we will feasibly colonise could be completely transformed through geoengineering processes. Likewise, the ability of humans to live in space could be enhanced through genetic modification interventions. Even if, however, the problems concerning survival in space were solved, we think that, at least in the first period of colonisation of space or other planets, giving birth to children in space could be a morally irresponsible choice since we argue, the life we ​​could give them might not be good enough. We contend that this is the case since when we decide to have a baby. We argue that it is not morally right to be content that our children have a minimally sufficient life worth living; before we give birth to children in space, we should make sure we can give them a reasonable chance of having a good life. This principle applies both on Earth - at least where you can choose - and for space travel.